Acylhydrazones as Reversible Covalent Crosslinkers for Self‐Healing Polymers. (27th April 2015) - Kuhl, Natascha; Bode, Stefan; Bose, Ranjita K.; Vitz, Jürgen; Seifert, Andreas; Hoeppener, Stephanie; Garcia, Santiago J.; Spange, Stefan; van der Zwaag, Sybrand; Hager, Martin D.; Schubert, Ulrich S.
Abstract : The utilization of dynamic covalent and noncovalent bonds in polymeric materials offers the possibility to regenerate mechanical damage, inflicted on the material, and is therefore of great interest in the field of self‐healing materials. For the design of a new class of self‐healing materials, methacrylate containing copolymers with acylhydrazones as reversible covalent crosslinkers are utilized. The self‐healing polymer networks are obtained by a bulk polymerization of an acylhydrazone crosslinker and commercially available methacrylates as comonomers to fine‐tune the T g of the systems. The influence of the amount of acylhydrazone crosslinker and the self‐healing behavior of the polymers is studied in detail. Furthermore, the basic healing mechanism and the corresponding mechanical properties are analyzed. Abstract : Acylhydrazone crosslinked polymer films are synthesized by the copolymerization of a new acylhydrazone crosslinker with different commercially available methacrylates. The self‐healing behavior of the damaged material is studied in detail with the help of differential scanning calorimetry, scratch testing experiments, profilometry, dynamic‐mechanical thermal analysis, and temperature dependent FT‐IR as well as solid state NMR measurements.